Hubungan Tingkat Kecemasan Dengan Kualitas Tidur Pada Penderita Asma Di Puskesmas Bekasi Jaya - Agustin, Khalda; Indrawati, Lina; Meriyandah, Hilda (PT. Pubsains Nur Cendekia, 2023)
Background: Asthma is a chronic non-communicable lung disease characterized by frequent and sudden asthma attacks. If individuals with asthma experience attacks as a heterogeneous disease, they will become dependent on medication and respiratory devices. Asthma does not have persistent symptoms but may experience exacerbations ranging from mild to severe, which can lead to death. Asthma exacerbations are marked by a progressive increase in symptoms such as shortness of breath, coughing, wheezing, chest tightness, and a progressive decline in lung function. Objective: This study aims to determine the relationship between anxiety levels and sleep quality among asthma patients at Bekasi Jaya Community Health Center in 2023. Methods: This quantitative study employed a cross-sectional design. The population consisted of all asthma patients at the health center, totaling 85 respondents. A total sampling technique was used to collect data. Results: The study results, with a 95% confidence level or a significance level of 5% (0.05), showed a p-value of 0.000, which is less than the significance level of 0.05. This indicates that the null hypothesis (H0) is rejected, meaning there is a relationship between anxiety levels and sleep quality among asthma patients at Bekasi Jaya Community Health Center in 2023. Conclusion: Based on the statistical analysis using the chi-square test, it can be concluded that there is a significant relationship between anxiety levels and sleep quality among asthma patients at Bekasi Jaya Community Health Center in 2023.